Impact of a Parent Text Messaging Program on Pre-Kindergarteners' Literacy Development - Sonia Q. Cabell; Tricia A. Zucker; Jamie DeCoster; Stefanie B. Copp; Susan Landry (SAGE Publishing, 2019)
There is increasing interest in low-cost, scalable approaches that support parent engagement in their children's learning at home. This study examined the impact of one such approach on pre-kindergarteners' literacy development during an academic year in a suburban public school setting that prioritized enrollment for children living in poverty. Parents were randomly assigned within children's classrooms to receive either: (a) a language and literacy text messaging program or (b) a health and well-being text messaging program. Unexpectedly, findings indicated that children entering the school year with higher skill levels benefited from the language/literacy program while those with lower initial skill levels benefited from the health/well-being program. Although this approach shows promise in impacting some children's literacy skills, it is clear that "one size" does not fit all families and that some families may benefit from text messages on basic needs such as sleep, nutrition, health, and behavior.